When We Ride - Ogle, Rex ([Place of publication not identified] : Norton Young Readers, 2025)
Rex Ogle explores bonds of loyalty and friendship and how they're tested by drugs and violence in this propulsive novel-in-verse.
new ya book 2025 spring.
Keywords: Mexican American teenage boys; Friendship in adolescence; Mexican Americans; Drug dealers; Schools; Single mothers; Best friends; Friendship; Social problems; Marijuana